Evaluasi Program Tahfidzul Qur’an Di Mushalla Firdaus Tilatang Kamang - Hadi Latif; Supratman Zakir; Darul Ilmi; Arif Septiawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Research This study aims to evaluate the Tahfidzul Qur'an program in Mushalla Firdaus Tilatang Kamang with the main purpose of assessing the effectiveness and efficiency of the program in achieving the program in achieving the target of memorizing the Qur'an of students. Evaluative research method used in evaluating the Tahfidzul Qur'an program at Mushalla Firdaus Tilatang Kamang is the CIPP model (Context, Input, Process, Product) model. The CIPP model is designed to provide a comprehensive framework framework in systematically assessing various aspects of the program. The results of this study show that the evaluation of the Tahfidzul Qur'an program at Mushalla Firdaus Tilatang Kamang shows positive and beneficial results despite some challenges. The context analysis highlighted the strong motivation of learners as well as support from the community, despite economic and social constraints. The input evaluation emphasized the importance of teachers' qualifications, an adequate curriculum, and improved facilities and financial support. The process of implementing a diverse program of teaching methods and classroom management is effective, but more individual guidance and technology integration are needed. The product evaluation revealed the program's success in achieving memorization targets, improving academic achievement, spiritual development, and positive character changes in learners. With continuous improvement and implementation of recommendations, this program has great potential to continue to grow and produce a generation of quality and characterful Qur'an memorizers.